State investment policy and today's investment environment in Uzbekistan - Murtazaev Nurbek Rashidovich (THE INNOVATION ECONOMY, 2026)
The article reflects the importance and essence of foreign investments in the development of the country's economy. It analyzes the current state of attracting foreign investments and presents proposals for measures to enhance their inflow